A time for dystopias (Colloquia Comparativa Litterarum, 2025)
This text is an introduction to the theme of this issue. First, it briefly overviews the place and the functions of the literary genre of dystopia in present-day world literature. It then outlines the history of the genre in Bulgarian literature from its almost complete absence until 1989 to the rise of a true dystopian wave in the second decade of the new century. In its last part, the text points out how the thirteen articles published inside can be divided into three groups in terms of their subject matter and disciplinary approach.
Keywords: dystopia; novel; 21st century; bulgarian literature